Apostrofere den levende: Den pårørendes vitnemål om autisme i Olaug Nilssens Tung tids tale - Haugen Warberg, Silje (K&K - Kultur og Klasse, 2021)
Olaug Nilssen’s Tung tids tale (2017) is a novel about speaking to and for the disabled and disarticulate child in the role as mother and caregiver. Olaug, the narrator, tells the story of her son Daniel’s regressive autism and of the challenges she meets as she tries to mediate between him and the outside world, in particular health personnel and other professional caregivers. The narration is directed towards Daniel himself, addressed as ”you”. Because Daniel is unable to use verbal language and reply, the address resembles the figure of the apostrophe. The communication circuit it generates is triangulated, involving both the ”I” that sends the message, the unresponsive ”you” who is unable to respond to it, and a third party intended to overhear it – in this case the implicit or historical readers of the text. In the article the functions of this address is explored in the light of how the novel thematizes caregiving as an act of witnessing. I argue that the apostrophic address produces an alternative to the novel’s narrative through the establishment of an aesthetic and rhetorical event constituted by the communicative situation itself. The address thus provides a formal way of handling the ethical and existential dimensions connected to Olaug’s role as caregiver and narrator in a text that speaks both for and to her son.